Creating authentic iPad activities to increase student engagement: A learning design approach. - Martin, Romana; Ostashewski, N.; Dickinson, Sonia (Association for the Advancement of Computing in Education (AACE), Chesapeake, VA, 2013)
This paper describes the design approach adopted for creating authentic iPad activities for use inclassroom settings with the aim of increasing student engagement. The challenge of this task was to also ensureequity for learners by designing learning activities that can be completed with or without an iPad. A pilotimplementation of the learning design approach in a classroom setting was received favorably and this has led toplans for a formal study trialing a range of learning designs. In theory, the results indicate that iPads can be usedsuccessfully for engaging students in authentic digital creation activities related to the content they are studying. Inpractice, a sequential process for the development of these learning activities was needed for implementation. Afive-step approach for adapting traditional learning designs to include iPad activities is outlined.